1985
DOI: 10.1113/jphysiol.1985.sp015855
|View full text |Cite
|
Sign up to set email alerts
|

Propagating potassium and chloride conductances during activation and fertilization of the egg of the frog, Rana pipiens.

Abstract: SUMMARY1. Fertilization or artificial activation of the frog egg (Rana pipiens) elicits a positive-going shift in membrane potential which results from an opening of Cl-and K+ channels in the egg membrane. We examined the spatial localization of the currents produced by the opening of these channels, using large patch electrodes (tip diameters 3-10 ,um). We also used small patch electrodes (tip diameters about 1 /Im) to study the single K+ channel currents.2. After activation, with the patch electrode at any p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 25 publications
3
5
0
1
Order By: Relevance
“…This was confirmed by RT-PCR analysis of early blastulas divided into animal and vegetal halves, using equal amounts of extracted mRNA (determined by amplifying the ubiquitous ornithine decarboxylase transcript; data not shown). These observations are consistent with a role for Cl --channel-mediated membrane potential changes to prevent polyspermy following fertilisation (Jaffe et al 1985). By stage 7, xCLIC transcripts appear to be localised to the centre of animal hemisphere cells (Fig.…”
Section: Resultssupporting
confidence: 79%
“…This was confirmed by RT-PCR analysis of early blastulas divided into animal and vegetal halves, using equal amounts of extracted mRNA (determined by amplifying the ubiquitous ornithine decarboxylase transcript; data not shown). These observations are consistent with a role for Cl --channel-mediated membrane potential changes to prevent polyspermy following fertilisation (Jaffe et al 1985). By stage 7, xCLIC transcripts appear to be localised to the centre of animal hemisphere cells (Fig.…”
Section: Resultssupporting
confidence: 79%
“…A small inward IS current occurred in 20 mM NaCl (g), but only outward IS current was generated in 20 mM NaI (h), indicating that not only the large and accelerative increase in inward current but also the IS current results from the opening of Clchannels on the egg plasma membrane. SB: tropicalis eggs is probably mediated by a wavelike opening of Cl − channels in response to the Ca 2+ wave, observed in frog fertilization (Jaffe, Kado, & Muncy, 1985;Kline & Nuccitelli, 1985). Thus, we found that monospermic fertilization of X. tropicalis was ensured by the positive-going fertilization potential which was mediated by the opening of CaCCs.…”
Section: Ca 2+ Waves During Xenopus Fertilizationsupporting
confidence: 53%
“…CaCCs on egg plasma membrane are probably activated in response to the Ca 2+ wave spreading from the sperm entry site because the positive‐going activation potentials similar to the fertilization potentials were elicited by an artificial increase in [Ca 2+ ] i with Ca 2+ ‐ionophore. The positive fertilization potential in X. tropicalis eggs is probably mediated by a wavelike opening of Cl − channels in response to the Ca 2+ wave, observed in frog fertilization (Jaffe, Kado, & Muncy, ; Kline & Nuccitelli, ). Thus, we found that monospermic fertilization of X. tropicalis was ensured by the positive‐going fertilization potential which was mediated by the opening of CaCCs.…”
Section: Discussionmentioning
confidence: 98%
“…By contrast, during fertilization in animals, studies have allowed the recording only of membrane currents and not that of the ions carrying them (30,31). Furthermore, most of these studies were performed with artificially activated rather than sperm-activated eggs (32). Sea urchin is the only system where current propagation was analyzed in detail during fertilization.…”
Section: Discussionmentioning
confidence: 99%